The The Relationship Between Cyberbullying And Self-Esteem In Adolescents At Global Edu High School - Maidartati, Maidartati; Irawan, Erna; Tania, Mery; Saputra, Anggi; Firdaus, Salsa Bila (International Journal of Health Sciences, 2024)
The rapid development of social media among teenagers has served as an easily accessible communication tool, creating new trends in society, namely cyberbullying. One's self-esteem is influenced by social relationships and how they feel valued. Many cases indicate that teenagers often experience low self-esteem, one of which is due to cyberbullying. This study aims to determine the relationship between cyberbullying and self-esteem in teenagers at Edu Global High School. The study employed a correlational design with a cross-sectional research approach. The population consisted of 61 active 10th-grade students at Edu Global High School, with 61 respondents as the research sample. The data collection technique used total sampling. Data collection employed two types of questionnaires, namely the Rosenberg Self-Esteem Scale (RSES) and the Cyberbullying and Online Aggression Survey Instrument. Data analysis utilized univariate analysis presented in the form of distribution and bivariate analysis using the Spearman correlation test. The results showed that in the case of cyberbullying, the majority (87%) were perpetrators with a low category (53 respondents), while the majority (82%) were also victims with a low category (50 respondents). Regarding self-esteem, the majority (67%) had high self-esteem (41 respondents) and almost entirely (33%) were in the low category (20 respondents). The research results indicated a p-value of 0.011 < 0.05, which means there is a significant relationship between cyberbullying and self-esteem in a negative direction, indicating that the higher the level of cyberbullying experienced by teenagers, the lower their self-esteem. In conclusion, this study found a significant negative relationship between cyberbullying and the self-esteem of teenagers at Edu Global High School. The higher the level of experienced cyberbullying, the lower their self-esteem. This emphasizes the importance of the role of nurses and the school in enhancing student self-esteem and addressing cyberbullying issues. These findings provide important insights into the impact of social media on teenagers. Therefore, it is hoped that nurses and the school authorities can work to help improve student self-esteem.